An inexpensive moist chamber culture technique for finding microbiota on live tree bark - Bordelon, Ashley P.; Keller, Harold W.; Scarborough, Angela R. (Applications in plant sciences, 2024)
Traditional moist chamber cultures (MCs) prepared in aseptic laboratory environments using sterile Petri dishes are commonly used to quantify the microbiota of rough-bark tree species and woody vines. MCs are typically expensive and may be difficult to make, so a less expensive option made from easily available supplies was developed. These cost-friendly MCs were compared with standard laboratory methods to demonstrate their efficacy. Modified MCs were made using inexpensive, store-bought supplies; compared to a standard laboratory setting, the modified MCs are shown to be less expensive with a faster setup time and larger size that facilitates a variety of tree and woody vine species. MC use resulted in the discovery of new species of fungi and myxomycetes with associated locality records. We provide detailed instructions for creating modified MCs, as well as a list of myxomycete species and their associated bark characteristics, pH values, and water-holding capacity. This new, low-cost MC technique makes the study of microbiota more inclusive and accessible for those in research laboratories, classrooms, and homes, including both amateurs and professionals. MCs are easy to prepare, versatile, and applicable for many areas of botany and the biological sciences, potentially allowing exploration into unexplored areas in urban ecosystems.